Mittereligioossus Eestis: põlvkondlik vaade - Remmel, Atko (Usuteaduslik Ajakiri, 2024)
Nonreligion in Estonia: generational approach Based on the interviews with the nonreligious in Estonia – where religion has been marginal in the public sphere for almost 60 years – the article explores generational differences among the nonreligious in their attitudes and sets of ideas about (non)religion. According to the findings, the paper argues that there are two types of nonreligion: one that emerges from contact with religion and characterizes mainly the older generation, and another one that emerges from the lack of contact and characterizes mainly the middle-aged and younger generation. As (non)religion is often considered a combination of identities, beliefs, and practices, the article argues that a central element of Estonian nonreligion is the normativity of nonreligion in society. This perception defines not only general attitude, but also the spheres of religion and nonreligion, so both are understood primarily as different solutions to personal well-being.